1976
DOI: 10.1042/cs0500349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenobarbitone on Plasma Lipids in Normal Subjects

Abstract: 1. Phenobarbitone in a dose of 180 mg daily was administered to ten normal subjects for 3 weeks. There was a significant increase in total plasma cholesterol, plasma low-density-lipoprotein cholesterol, plasma low-density-lipoprotein (LDL) triglycerides and plasma LDL protein. The increase in plasma LDL cholesterol accounted for the increase in total plasma cholesterol. There was a significant reduction in the ratio of LDL cholesterol to LDL protein. 2. No significant changes were observed in total plasma trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The increase in plasma and LDL apolipoprotein B concentrations after the administration of phenobarbitone for 3 weeks confirms the earlier observations that phenobarbitone affects LDL metabolism in man (Miller & Nestel, 1973;Durrington et al, 1976a). In the present study, an increase in serum HDL cholesterol was also found.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The increase in plasma and LDL apolipoprotein B concentrations after the administration of phenobarbitone for 3 weeks confirms the earlier observations that phenobarbitone affects LDL metabolism in man (Miller & Nestel, 1973;Durrington et al, 1976a). In the present study, an increase in serum HDL cholesterol was also found.…”
Section: Discussionsupporting
confidence: 93%
“…Total plasma cholesterol and triglycerides, plasma very-low-density lipoprotein (VLDL) cholesterol, triglycerides and protein and LDL cholesterol, triglycerides and protein, antipyrine clearance and serum y-glutamyl transpeptidase were the subject of an earlier report (Durrington et al, 1976a). The present study concerns concentrations of total plzsma apolipoprotein B and plasma VLDL and LDL apolipoprotein B and of plasma HDL cholesterol measured initially and at the end of the period on phenobarbitone.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies on anticonvulsants have demon strated elevated serum cholesterol and triglycer ide levels in healthy subjects and patients with epilepsy (4,12,16). High plasma HDL choles terol levels have been measured in subjects undergoing phenytoin treatment (15).…”
Section: Introductionmentioning
confidence: 99%